Maternity protection for female non-standard workers in South Africa: the case of domestic workers - Catherine Pereira-Kotze; Tanya Doherty; Mieke Faber (BMC, 2022)
Abstract Background Many women work in positions of non-standard employment, with limited legal and social protection. Access to comprehensive maternity protection for all working women could ensure that all women and children can access health and social protection. This study aimed to describe the maternity protection benefits available to women in positions of non-standard employment in South Africa, using domestic workers as a case study. Methods A qualitative descriptive study design was used. National policy documents containing provisions on maternity protection were identified and analysed. Interviews were conducted with purposively selected key informants. Data extracted from published policy documents and information obtained from interviews were triangulated. A thematic analysis approach was used for evaluation of policy content and analysis of the interviews. Results Twenty-nine policy and legislative documents were identified that contain provisions on maternity protection relevant to non-standard workers. These documents together with three key informant interviews and two media releases are used to describe availability and accessibility of maternity protection benefits for non-standard workers in South Africa, using domestic workers as a case study. Maternity protection is available in South Africa for some non-standard workers. However, the components of maternity protection are dispersed through many policy documents and there is weak alignment within government on maternity protection. Implementation, monitoring, and enforcement of existing maternity protection policy is inadequate. It is difficult for non-standard workers to access maternity protection benefits, particularly cash payments. Some non-standard workers have unique challenges in accessing maternity protection, for example domestic workers whose place of work is a private household and therefore difficult to monitor. Conclusion The heterogeneity of non-standard employment makes it challenging for many women to access maternity protection. There are policy amendments that could be made and improvements to policy implementation that would enhance non-standard workers' access to maternity protection. Potential long-term benefits to women and children's health and development could come from making comprehensive maternity protection available and accessible to all women.